2005
DOI: 10.1081/pln-200025834
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Nitrogen, Phosphorus, Potassium, and Sulphur Effects on Forage Yield and Quality of Timothy Hay in the Parkland Region of Saskatchewan, Canada

Abstract: For producers in the Parkland zone of Canadian prairies, timothy (Phleum pratense L.) hay provides another opportunity for crop

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…At three sites in the Parkland region with just one cut of timothy each year, maximum yields of 8 to 10 Mg ha (1 were obtained with application of 101 to 157 kg N ha (1 (Malhi et al 2004). The higher N requirement in our study was possibly due to the immobilization of N in soil organic matter during the initial years of a perennial grass stand (Bremer et al 2002).…”
Section: Rate Of N Fertilizermentioning
confidence: 81%
See 4 more Smart Citations
“…At three sites in the Parkland region with just one cut of timothy each year, maximum yields of 8 to 10 Mg ha (1 were obtained with application of 101 to 157 kg N ha (1 (Malhi et al 2004). The higher N requirement in our study was possibly due to the immobilization of N in soil organic matter during the initial years of a perennial grass stand (Bremer et al 2002).…”
Section: Rate Of N Fertilizermentioning
confidence: 81%
“…Phosphorus application significantly increased fibre concentrations of first-cut forage, but did not affect in vitro digestibility (NDF30) ( Table 4). In comparison, Malhi et al (2004) found that P application did not affect fibre concentrations.…”
Section: Phosphorus Experimentsmentioning
confidence: 92%
See 3 more Smart Citations